THE IMPLEMENTATION OF TEACHING SPEAKING IN THE THERAPY 1 PROGRAM AT ELFAST ENGLISH COURSE PARE KEDIRI - riawati, cantik (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aims of this research are to describe the teaching speaking in the Therapy 1 program at ELFAST English Course Pare â€“ Kediri. There were 5 points of research focuses, those are: 1) the background study of tutor ad the students in â€œThe Therapy 1 classâ€, 2) the teaching speaking of â€œThe Therapy 1 classâ€ at ELFAST English Course in the terms of: curriculum, syllabus, lesson plan, materials, media, and the technique, 3) the implementation of teaching speaking in â€œThe Therapy 1 classâ€ in the terms of: pre teaching, whilst teaching and post teaching, 4) the teacherâ€™s evaluation and 5) Studentâ€™s score. The subjects of research were the teacher of the class and the students of The Therapy 1 B class, there were 7 students of the class. This research use descriptive qualitative, because the teaching speaking in the Therapy 1 Program was so unique, it was different from other course, therefore it was used this descriptive qualitative research. The methods used in collecting data were interview, observation and documentation. The result of study showed on the finding research, the Teaching Speaking in the Therapy 1 program at ELFAST English Curse Pare â€“ Kediri was good by score 80%, because just some point that was not appropriate maximally and other was maximal appropriate with the theory.